Applied Project-Based Learning in a Construction Materials Course [Aprendizaje Basado en Proyectos Aplicados en la Asignatura de Materiales de Construcción] - Espinoza-Oyarzun, J; Rementeria-Pinones, J; Burgos-Leiva, C; Burgos-Leiva, C; Rodriguez-Garcia, A; Rodriguez-Garcia, A (Centro de Informacion Tecnologica, 2021)
The primary objective of this research study was to implement a project-based learning (PBL) methodology to improve knowledge appropriation, teamwork skills, and collaboration between students. The methodology was applied by using an in-class experiment in the building materials course of the technology in construction degree at the University of Santiago of Chile. For the in-class experiment, Radiata and Oregon pinewoods were dried for 48 hours to assess changes in mass. The results showed that in-group learning increased 39.1% after taking into account student final grades and average entry grades. Student environmental assessment and student community life commitments were shared in classroom interventions. It is concluded that student teamwork and collaborative skills improved significantly. © 2021. All rights reserved.